PENGARUH PENANAMAN MODAL ASING (PMA), PENANAMAN MODAL DALAM NEGERI (PMDN) DAN INFLASI TERHADAP PENERIMAAN PAJAK DI INDONESIA TAHUN 2014-2023 - Setyanto, Alief; Sari, Meylika Juwita; Anastasya, Sari (Laboratorium Riset Ekonomi, 2024)
taxes are an important component of a country's wealth and monetary level, enabling the country to produce output in the form of state revenue. The study aims to determine the effect between foreign investment, domestic investment and inflation on tax revenue in Indonesia. This study was conducted with the aim of knowing what factors can affect tax revenue in Indonesia, which is also the main source of tax revenue in Indonesia. This study uses quantitative methods with an associative approach while the analysis method used is multiple linear regression analysis. The results obtained from this study are that tax revenue in Indonesia is negatively affected by the variables of foreign investment, domestic investment and inflation.